2024
DOI: 10.1101/2024.02.05.579044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholinergic modulation of interhemispheric inhibition in the mouse motor cortex

Takashi Handa,
Qing Zhang,
Hidenori Aizawa

Abstract: Interhemispheric inhibition (IHI) of the homotopic motor cortex is believed to be effective for accurate unilateral motor function. However, the cellular mechanisms underlying IHI during unilateral motor behavior remain unclear. Furthermore, the impact of the neuromodulator acetylcholine (ACh) on IHI and the associated cellular mechanisms are not well understood. To address this knowledge gap, we conducted recordings of neuronal activity from the bilateral motor cortex of mice during the paw-reaching task. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For example, when the brain or the spinal cord is injured, the brain often recruits normally-underused cortical sensorimotor areas (dorsal premotor cortex [PMd], primary motor cortex [M1], primary somatosensory cortex [S1], and superior parietal cortex of Area 2) during ipsilateral hand/finger movements (Grefkes & Fink, 2020; Hoy et al, 2004; Jang et al, 2004; Lotze et al, 2006; Ward et al, 2008). Recently, animal studies have suggested that such recruitment of ipsilateral sensorimotor cortices is mediated by disinhibition of interhemispheric inhibition between the left and right motor cortices (Yamaguchi et al, 2023) by acetylcholine modulating GABAergic interneurons (Handa et al, 2024). In stroke patients, jamming transcranial magnetic stimulation (TMS) to the ipsilateral sensorimotor cortices disrupts finger movement, especially the TMS to the PMd disrupts the movement more than when it is applied to the M1 and the superior parietal lobule (Lotze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when the brain or the spinal cord is injured, the brain often recruits normally-underused cortical sensorimotor areas (dorsal premotor cortex [PMd], primary motor cortex [M1], primary somatosensory cortex [S1], and superior parietal cortex of Area 2) during ipsilateral hand/finger movements (Grefkes & Fink, 2020; Hoy et al, 2004; Jang et al, 2004; Lotze et al, 2006; Ward et al, 2008). Recently, animal studies have suggested that such recruitment of ipsilateral sensorimotor cortices is mediated by disinhibition of interhemispheric inhibition between the left and right motor cortices (Yamaguchi et al, 2023) by acetylcholine modulating GABAergic interneurons (Handa et al, 2024). In stroke patients, jamming transcranial magnetic stimulation (TMS) to the ipsilateral sensorimotor cortices disrupts finger movement, especially the TMS to the PMd disrupts the movement more than when it is applied to the M1 and the superior parietal lobule (Lotze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, this bilateral mode is the first step toward restoring motor function (Grefkes and Fink, 2020). Recent animal studies have suggested that this bilaterally active mode is caused by disinhibition of interhemispheric inhibition between the left and right motor cortices (Yamaguchi et al, 2023) by acetylcholine modulating GABAergic interneurons (Handa et al, 2024).…”
Section: Introductionmentioning
confidence: 99%